Nursing of an adult patient with Fabry disease (1例成人罕见法布里病患者的护理) - YU Weiwei (余卫卫); YU Lingling (于玲玲); CHEN Ting (陈婷) (Association of Integrative Nursing, 2022)
This paper summarized the nursing interventions for an adult patient with Fabry disease. Key issues of nursing included medication care during intravenous therapy of Agalsidase Beta, pain and fever control, prevention of unintentional injury, symptom management, dietary guideline and psychological care of patient and family members. (本文总结1例成人罕见法布里病(FD)患者的护理经验。护理要点包括: 做好注射用阿加糖酶β静脉治疗过程中的用药护理、发热疼痛护理、防止意外伤害、症状管理、饮食指导以及患者及家属的心理护理。)